Development of the Computer-Adaptive Version of the Late-Life Function and Disability Instrument - McDonough, Christine M. (Oxford University Press, 2012)
BACKGROUND. Having psychometrically strong disability measures that minimize response burden is important in assessing of older adults. METHODS. Using the original 48 items from the Late-Life Function and Disability Instrument and newly developed items, a 158-item Activity Limitation and a 62-item Participation Restriction item pool were developed. The item pools were administered to a convenience sample of 520 community-dwelling adults 60 years or older. Confirmatory factor analysis and item response theory were employed to identify content structure, calibrate items, and build the computer-adaptive testings (CATs). We evaluated real-data simulations of 10-item CAT subscales. We collected data from 102 older adults to validate the 10-item CATs against the Veteran’s Short Form-36 and assessed test–retest reliability in a subsample of 57 subjects. RESULTS. Confirmatory factor analysis revealed a bifactor structure, and multi-dimensional item response theory was used to calibrate an overall Activity Limitation Scale (141 items) and an overall Participation Restriction Scale (55 items). Fit statistics were acceptable (Activity Limitation: comparative fit index = 0.95, Tucker Lewis Index = 0.95, root mean square error approximation = 0.03; Participation Restriction: comparative fit index = 0.95, Tucker Lewis Index = 0.95, root mean square error approximation = 0.05). Correlation of 10-item CATs with full item banks were substantial (Activity Limitation: r = .90; Participation Restriction: r = .95). Test–retest reliability estimates were high (Activity Limitation: r = .85; Participation Restriction r = .80). Strength and pattern of correlations with Veteran’s Short Form-36 subscales were as hypothesized. Each CAT, on average, took 3.56 minutes to administer. CONCLUSIONS. The Late-Life Function and Disability Instrument CATs demonstrated strong reliability, validity, accuracy, and precision. The Late-Life Function and Disability Instrument CAT can achieve psychometrically sound disability assessment in older persons while reducing respondent burden. Further research is needed to assess their ability to measure change in older adults.